Pengaruh Media Pembelajaran Quizizz terhadap Hasil Belajar Biologi Siswa - Alonemarera, A. S. Alonemarera; Ardhi, Ainan Yasra; Ainurrahman Ainurrahman; Ulfaidah Ulfaidah; Dayanti, Sri; Eni Eni (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study was motivated by students’ low conceptual understanding and learning outcomes in biology, a subject that tends to be abstract and is still predominantly taught using the lecture method. Additionally, the use of innovative learning media remains suboptimal. This study aims to analyze the effect of using Quizizz-based learning media on students’ biology learning outcomes. The method used is a Systematic Literature Review (SLR), involving the steps of formulating research questions, collecting relevant literature, conducting selection and classification, analyzing, and interpreting findings from various previous studies. Data were obtained from scientific articles accessed through databases such as Google Scholar and Elicit. The findings of the review indicate that the consistent use of Quizizz has a positive effect on student learning outcomes, as evidenced by an increase in average scores, significant differences between the experimental and control classes, and increased motivation and engagement in learning. Furthermore, Quizizz’s interactive features, provision of immediate feedback, and creation of an enjoyable learning atmosphere contribute to more effective understanding of biological concepts. Thus, the Quizizz learning platform can serve as an innovative and creative alternative for enhancing the quality of biology instruction and student learning outcomes.